Adenosine A3 receptors mediate hypotension in the angiotensin II-supported circulation of the pithed rat. - Fozard, J. R. (Nature Publishing Group, 1993)
The cardiovascular effects of N6-2-(4-aminophenyl)ethyladenosine (APNEA), which when radiolabelled with 125I shows high affinity for the newly described adenosine A3 receptor, have been investigated in the angiotensin II-supported circulation of the pithed rat. APNEA induces hypotensive responses which are unaffected by high doses (20-40 mg kg-1) of the broad spectrum, adenosine receptor antagonist, 8-(p-sulphophenyl)theophylline (8-SPT). 8-SPT-resistant falls in blood pressure are also seen, in the absence of bradycardia, with 5'-N-ethylcarboxamidoadenosine (NECA) and the R- and S-enantiomers of N6-phenylisopropyladenosine (PIA). Xanthine insensitivity, high potencies of APNEA, NECA and R-PIA, and an enantiomeric selectivity favouring R- over S-PIA are distinguishing features of the adenosine A3 receptor. We suggest that hypotension in the pithed rat may be a functional correlate of this site.